The use of technology in hybrid learning for student with special needs - Ade Putri Sarwendah; Nur Azizah; Mumpuniarti Mumpuniarti (Intelektual Pustaka Media Utama, 2023)
This study aims to describe the use of technology in learning for students with special needs during the transition period after the COVID-19 pandemic to the new normal. This study is descriptive research with a survey method. The survey was conducted with 41 special education teachers with variety of special needs students. Data is collected using Google Form questionnaires. Data analysis is carried out by calculating the frequency and is presented as percentages. Participants in this study were chosen randomly for data variation. The presentation of data is carried out qualitatively based on the respondents’ answers to the questions asked. The study participants argued that hybrid learning was feasible, even though it was recognized as encountering obstacles. Based on the results of a survey conducted by special education teachers at special education school (SLB), for hybrid learning, digital platforms are used to support online learning. The platforms used are WhatsApp and video conferencing, such as Google Meet. Integrating technology is considered important for teachers to support the learning process. Conscious and planned efforts and teacher motivation are critical to increasing their experience and skills in utilizing technology in learning.